2018
DOI: 10.1039/c8dt02903b
|View full text |Cite
|
Sign up to set email alerts
|

New gold pincer-type complexes: synthesis, characterization, DNA binding studies and cytotoxicity

Abstract: With the aim of assessing whether Au(iii) compounds with pincer type ligands might be utilized as potential antitumor agents, three new monofunctional Au(iii) complexes of the general formula [Au(N-N'-N)Cl]Cl2, where N-N'-N = 2,6-bis(5-tert-butyl-1H-pyrazol-3-yl)pyridine (H2LtBu, 1), 2,6-bis(5-tert-butyl-1-methyl-1H-pyrazol-3-yl)pyridine (Me2LtBu, 2) or 2,6-bis((4S,7R)-1,7,8,8-tetramethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine (Me2*L, 3) were synthesized. All complexes were characterized by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…The cytotoxicity of complex 1 and its ligand was partially tested on cell lines of colon carcinoma (LS-174), lung carcinoma (A549) and melanoma (A375) cell lines. The results of this study have shown that complex 1 exhibited stronger anti-tumor effect on all three types of tumor cells tested compared to cisplatin [15]. Since some compounds may show delayed toxicity, it is concluded that the analysis of cytotoxicity should be performed after an interval of at least 48 hours [20].…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The cytotoxicity of complex 1 and its ligand was partially tested on cell lines of colon carcinoma (LS-174), lung carcinoma (A549) and melanoma (A375) cell lines. The results of this study have shown that complex 1 exhibited stronger anti-tumor effect on all three types of tumor cells tested compared to cisplatin [15]. Since some compounds may show delayed toxicity, it is concluded that the analysis of cytotoxicity should be performed after an interval of at least 48 hours [20].…”
Section: Resultsmentioning
confidence: 81%
“…The synthesis and characterization of 2,6-bis(5-tert-butyl-1H-pyrazol-3-yl)pyridine (H2L tBu ), 2,6-bis(5-tert-butyl-1-methyl-1H-pyrazol-3-yl)pyridine (Me2L tBu ), and 2,6bis((4S,7R)-1,7,8,8-tetramethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine (Me2*L) was discussed in detail in previously published article [15]. The newly synthesized complexes, namely [Au(H2LtBu)Cl]Cl2 (1), [Au(Me2LtBu)Cl]Cl2 (2) and [Au(Me2*L)Cl]Cl2…”
Section: Synthesis Of Au(iii) Pincer Complexes With Three Bispyrazolamentioning
confidence: 99%
See 1 more Smart Citation
“…The same conclusion was derived for structurally similar complexes with terpyridine ligands (Liu et al, 1995;Messori et al, 2005;Shi et al, 2006). The other method, fluorescence spectroscopy, was employed in the aim to clarify the mode 1 | The DNA-binding constants (K b ) and Stern-Volmer constants (K sv ) from EB-DNA fluorescence for complexes 1-9 and bovine serum albumin (BSA) constants and parameters (K sv , k q , K, and n) derived for complexes 4-9 (Radisavljević et al, 2018(Radisavljević et al, , 2019.…”
Section: Biological Targets For Gold(iii) Complexesmentioning
confidence: 87%
“…The interactions between newly synthesized gold(III) complexes that contain structurally distinct nitrogen-donor ligands (Figure 1), such as 2,6-bis(5-tert-butyl-1H-pyrazol-3-yl)pyridine (complex 1), 2,6-bis(5-tert-butyl-1-methyl-1H-pyrazol-3yl)pyridine (complex 2), 2,6-bis((4S, 7R)−1,7,8,8-tetramethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine (complex 3), 1,4-diaminobutane (complexes 4 and 7), 1,6diaminohexane (complexes 5 and 8), 1,8-diaminooctane (complexes 6 and 9), combination of 2,2 ′ -bipyridine and N-(3-((4-nitrophenyl) thio)phenyl)methanediimine (complex 10), and (Z)-1-(4-morpholinophenyl)-N-((4-(trifluoromethyl) pyrimidin-2-yl)methyl)methanimine (complex 11) (Radisavljević et al, 2018(Radisavljević et al, , 2019Sankarganesh et al, 2019;Tabrizi et al, 2020), and primary biomolecules were examined by different experimental methods. These complexes were selected having in mind that the presence of different nitrogen-donor inert ligands in the structure of some gold(III) complexes have great potential to stabilize metal ion and improve its binding affinity toward biomolecules under physiological conditions (Radisavljević et al, 2019).…”
Section: Biological Targets For Gold(iii) Complexesmentioning
confidence: 99%